The Goldfinch - Tartt, Donna (New York : Little, Brown and Company, 2013)
"The author of the classic bestsellers The Secret History and The Little Friend returns with a brilliant, highly anticipated new novel. A young boy in New York City, Theo Decker, miraculously survives an accident that takes the life of his mother. Alone and abandoned by his father, Theo is taken in by a friend's family and struggles to make sense of his new life. In the years that follow, he becomes entranced by one of the few things that reminds him of his mother: a small, mysteriously captivating painting that ultimately draws Theo into the art underworld. Composed with the skills of a master, The Goldfinch is a haunted odyssey through present-day America, and a drama of almost unbearable acuity and power. It is a story of loss and obsession, survival and self-invention, and the enormous power of art"--
Keywords: Young men -- Fiction; Loss (Psychology) -- Fiction; Artists -- Fiction; Self-realization -- Fiction; FICTION / Literary; New York (N.Y.) -- Fiction; Bildungstromans; Suspense fiction